2004
DOI: 10.1182/blood.v104.11.62.62
|View full text |Cite
|
Sign up to set email alerts
|

MOZ-TIF2, but Not BCR-ABL, Confers Properties of Leukemic Stem Cells to Committed Murine Hematopoietic Progenitors.

Abstract: The existence of leukemia stem cells has been demonstrated in acute myeloid and lymphoblastic leukemias (AML and ALL). The origins of these cells are unknown, but it has been suggested that they result from the transformation of adult hematopoietic stem cells (HSC). To challenge this hypothesis we tested the ability of representative leukemia oncogenes to transform committed myeloid progenitor cells that lack the capacity for self-renewal. Flow-sorted populations of common myeloid progenitors (CMP), and granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 0 publications
3
87
1
2
Order By: Relevance
“…Consecutive repetition of such assays (replating) can result in the isolation of subpopulations of hematopoietic cancer cells with self-renewal ability and also allows determination of whether genes of interest have the potential to confer selfrenewal activity in non-transformed hematopoietic cells. 22,23 Spheroid formation assays were performed originally to isolate neural stem or progenitor cells and are now often used to evaluate stem-like characteristics of tumor cells. Suspension culture in medium not containing serum but supplemented with basic fibroblast growth factor and epidermal growth factor allows the isolation of tumor cells with self-renewal capacity.…”
Section: Methods For Isolation Of Cscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consecutive repetition of such assays (replating) can result in the isolation of subpopulations of hematopoietic cancer cells with self-renewal ability and also allows determination of whether genes of interest have the potential to confer selfrenewal activity in non-transformed hematopoietic cells. 22,23 Spheroid formation assays were performed originally to isolate neural stem or progenitor cells and are now often used to evaluate stem-like characteristics of tumor cells. Suspension culture in medium not containing serum but supplemented with basic fibroblast growth factor and epidermal growth factor allows the isolation of tumor cells with self-renewal capacity.…”
Section: Methods For Isolation Of Cscsmentioning
confidence: 99%
“…8,38 On the other hand, some studies have suggested that the cells of origin for mouse AML stem cells are not only restricted to HSCs but also include progenitor cells committed to the myeloid lineage using bone marrow transplantation (BMT) model. 22,39 In the case of B acute lymphoblastic leukemia (B-ALL), although CSCs were found in cell subpopulations expressing HSC markers or B cell markers, [40][41][42][43][44] the cells of origin for B-ALL stem cells remain unclear. We recently established a Myc-induced mouse model of pre-B-ALL based on BMT model.…”
Section: Cells Of Origin For Cscsmentioning
confidence: 99%
“…Huntly et al 63 HSC from a knock-in locus does not. 60 As pointed out above, the results from the mouse models are obtained in the setting of perturbed hematopoiesis, and are confounded by retroviral insertional mutagenesis, the poorly controlled expression levels of the oncogenes and the spontaneous acquisition of additional mutations.…”
Section: F I G U R E 3 Cartoon Showing the Cells Of Origin Of Leukemimentioning
confidence: 99%
“…In spite of the fundamental difference between stem cells and their progenitors in self-renewal ability, we and others have shown that phenotypically and genetically indistinguishable cancers, including MLL-rearranged leukemia, can arise from not only stem cells, but also their immediate downstream short-lived progenitors with distinctive transcriptional programs So et al, 2003;Huntly et al, 2004;Krivtsov et al, 2006;Visvader, 2011;Blanpain, 2013). Consistently, gene expression signatures associated with stem cells and progenitors correlate with different clinical outcomes in AML (Eppert et al, 2011;Krivtsov et al, 2013).…”
Section: Introductionmentioning
confidence: 60%
“…Most of the current targeted therapies and their intended clinical utility are developed without considering the cancer cells of origin, which can have distinctive self-renewal and transcriptional properties. This traditional view has been challenged by the identification of phenotypically indistinguishable leukemia from different cells of origin So et al, 2003;Huntly et al, 2004), which exhibit different responses to standard chemotherapy treatment ( A, B Venn diagram showing the overlap of 33 commonly enriched up-regulated (A) and 38 commonly enriched down-regulated (B) highly significant (FDR < 0.05) gene sets between indicated comparisons (i.e., b-catenin inactivation in Hoxa9 À/À LSK-MLL-ENL, Hoxa9 inactivation in Ctnnb1 À/À LSK-MLL-ENL cells), including "Hoxa9/ Meis1_DN" (Hess et al, 2006), "LSC_mainentence_down" (Somervaille et al, 2009), "Hoxa9/Meis1_UP" (Hess et al, 2006), and "LSC_maintenance_up" (Somervaille et al, 2009) as indicated. C A small set of genes is synergistically regulated by b-catenin and Hoxa9 (the effect of knockout of both genes is smaller or larger than could have been predicted from their single knockouts).…”
Section: Discussionmentioning
confidence: 99%